(untitled) (LACCEI, 2024)
Wind and photovoltaic energy are the most widely used renewable energy sources because they are clean, inexhaustible, and suitable for applications in agriculture. This project is applied considering the needs of rural towns in Peru, where they do not have conventional electricity and lack of water in their crops. Therefore, the objective of this work is to select the most efficient renewable energy for the pumping system in agricultural applications. The results show the viability of both renewable energies, where the photovoltaic source is more economical. Consequently, this type of system is recommended for pump system applications in agriculture applications.